2011
DOI: 10.1309/ajcp4rk2ihvkttzv
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Circulating Cell-Free DNA Levels by a New Simple Fluorescent Test in Patients With Primary Colorectal Cancer

Abstract: Elevated circulating cell-free DNA (CFD) levels were found in patients with cancer. The standard CFD assays are work-intensive and expensive. The aim was to evaluate in patients with cancer a new simple CFD assay. In mice inoculated with cancer cells, CFD levels correlated with tumor size. Compared with healthy subjects, 38 patients with colorectal cancer (CRC) had higher preoperative CFD levels (798 ± 409 vs 308 ± 256 ng/mL; P < .0001). Compared with patients free of disease at 1 year, CFD levels were elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 14 publications
6
60
0
Order By: Relevance
“…In general, the levels are higher in mCRC patients than in healthy controls, as shown in Table 1 [15,20,47,58,[63][64][65][66][67][68][69][70][71][72]; and the levels have some correlation to stage as reported in a limited number of studies [15,41,68,73] in primary CRC. These findings give important biological information, and researchers suggest that cfDNA has potential as a diagnostic or screening tool; a potential that is currently being investigated by several groups.…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…In general, the levels are higher in mCRC patients than in healthy controls, as shown in Table 1 [15,20,47,58,[63][64][65][66][67][68][69][70][71][72]; and the levels have some correlation to stage as reported in a limited number of studies [15,41,68,73] in primary CRC. These findings give important biological information, and researchers suggest that cfDNA has potential as a diagnostic or screening tool; a potential that is currently being investigated by several groups.…”
Section: Methodsmentioning
confidence: 71%
“…It is therefore relevant to analyze the relation between cfDNA and CEA. As illustrated from the summary in Table 2, there is considerable variation in the measures, methods and parameter used to compare or combine the information from CEA and cfDNA analysis [15,20,32,33,39,41,[65][66][67][68][69][70][71][72][81][82][83]. The table includes studies identified by a systematic literature search of circulating DNA in CRC (all stages) as illustrated by Supplementary Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, during necrosis, apoptosis, autophagy and mitochondrial catastrophe, the tumour cells release DNA fragments of different sizes, which leads to raised levels of circulating cell-free DNA with longer fragments in serum or plasma 21. These studies have shown the existence of elevated levels of circulating cell-free DNA, probably released from cancer cells into the plasma or serum, which occurs in several types of cancer, such as lung,13 14 22 23 renal,9 prostate,28 29 breast,16 19 21 26 27 and CRC 15 18 20 25…”
Section: Introductionmentioning
confidence: 99%
“…This is the fourth study based on our innovative and simple technique to measure CFD levels in cancer patients [17][18][19]. Various complex techniques have been used to evaluate CFD concentrations, fragmentation, mutations, and epigenetic changes in cancer patients, including RCC.…”
Section: Discussionmentioning
confidence: 99%